A Protocol for Patient Education Based on Andragogy: A Convergent Parallel Mixed Methods Study - Mohtasham Ghaffari; Sakineh Rakhshanderou; Reza Negarandeh; Negin Niksadat; Ali Ramzankhan; Ali Vasheghani Farahani (Journal of Community Health Research)
Background: Patients' education is a key factor in patients' care. The purpose of this study is to design a protocol for a convergent parallel mixed methods study to explore the experiences of patients about their received educations based on andragogy model. Methods: This convergent parallel mixed method study includes two parallel quantitative and qualitative phases. During the quantitative phase, a cross-sectional survey will be conducted on 350 adult patients who had the history of hospitalization and received patient education from selected hospitals of Tehran, Iran. Sampling method will be random, and data collection tool will be a researcher-made questionnaire based on the principles of andragogy. The questionnaire’s validity and reliability are also measured, and data will be analyzed using SPSS 16. The qualitative phase will be conducted on adult patients who will be recruited purposively with maximum variation from the selected hospitals. Data will be gathered through semi-structured interviews and analyzed by directed content analysis. With regard to mixed method and using aligning convergence method, the results of the two sets of data will be compared or merged to see if the findings confirm or disconfirm each other. In this parallel section, the similarities between quantitative and qualitative results for assessing patient education are discussed and adapted to suit each other based on andragogy. Conclusions: The findings of this study will provide information regarding defects in patient education, suggesting that the principles of andragogy will develop patient education programs.